The story of India - Wood, Michael, 1948-; Jeffs, Jeremy; PBS Home Video; Maya Vision International ([London] : Distributed by PBS Home Video, 2008)
Historian Michael Wood chronicles the history of the Indian subcontinent, the richness and diversity of its peoples, and its continuing relevance in today's world.
Disc 2. Freedom. The power of ideas ; Spice routes and silk roads -- Disc 2. Ages of gold ; The meeting of two oceans ; Freedom.
Region 1; widescreen (enhanced); Dolby Digital 5.1 surround.
Special feature: The sights and sounds of India.
Filmed by Jeremy Jeffs ; edited by Gerry Branigan; original music by Howard Davidson & the Royal Philharmonic Orchestra; featured music by Ar Rahman ; written by Michael Wood ; directed by Jeremy Jeffs ; produced by Rebecca Dobbs.
Presented by Michael Wood.
Six-part BBC television series originally broadcast in 2007.
Not rated.
Keywords: Democracy -- Developing countries; India -- History; India -- Civilization; India -- Description and travel; India -- Social life and customs; Historical television programs; Nonfiction television programs; Television programs for the hearing impaired; Ethnic (Nonfiction) -- Television